Discover the Digital Technology Application in Fashion Business Models (Journal of Fiber Bioengineering and Informatics, 2020)
In the last few decades, there has been a surge of interest in the development of fashion businessmodels to assist fashion companies in reducing the cost and to efficiently manage business processes.These business models are developed to manage the internal operations within the company throughadopting complex formulae and algorithms to reduce the waste at each procedure. However in today’sfashion business market, global sourcing and global corporation are much more important than before.The relationship between the fashion company and its suppliers, the relationship between the fashioncompany and its customers, and the management of these relationships. All of them are crucial partsin the business strategy. The competition between fashion companies is no longer in company level butinstead is supply chain versus supply chain. Trying to take the massive information into considerationby using traditional digital technology is not a wise decision when developing business strategy. Furtherthinking, the information flow through the supply chain has the same characteristics “5Vs” as big data:Volume, Velocity, Variety, Value and Veracity. Put another word: the management of information flowin supply chain is the management of big data. There is no doubt that the digital technology under bigdata environment will fundamentally change the whole supply chain.The first objective of this paper is to identify the key weakness of lean and agile logistic supply chainmodels in literature. The second objective is to point out the technology challenges to develop theTomorrow’s models which build an agile response upon a lean platform: How to set up virtual networksfrom the early designing stage to the last consuming and feedback stage? How to set up the informationstandardization and synchronisation process in the system? How to specify the consumer requirementsin fitting effects and functional performance of garments? The last objective is to discover the digitaltechnology under big data environment which enable the information efficiently to flow through thewhole supply chain.